State Protection and Promotion of the Sami and Frisian Languages in the European Charter for Regional or Minority Languages Reports: A comparative study of Germany, the Netherlands, Norway, and Sweden - Wijnia, Danique (UiT Norges arktiske universitet, 2023)
This thesis discusses the protection and promotion of Indigenous and minority languages by analyzing the European Charter for Regional or Minority Languages (ECRML). The study is comparative in nature and focuses on the Sami languages, in Norway and Sweden, and the Frisian languages, in Germany and the Netherlands. The ECRML and its explanatory report are analyzed as well as the latest complete cycle of reports made by the states, the Committee of Experts (COMEX), and the Committee of Ministers. This limiting of the number of documents is necessary to constrain the scope of the thesis and still allow insights in the protection and promotion of the Sami and Frisian languages by these four states. The comparative nature of the study is found in the comparison of the states’ approaches to the protection and promotion of the languages in relation to the ECRML. This sheds some light on the differences and similarities between the states’ approaches to and compliance with the ECRML. The main goal of this thesis is to understand how the linguistic rights of the Sami and Frisians, that are stated in the ECRML, are addressed and followed up in the respective states in terms of protection and promotion in the primary educational sphere. The importance of this thesis lies in the creation of understanding of the similarities and differences in approaches that the four states employ to protect and promote the Sami and Frisian languages as well as what one can learn from these approaches in terms of state compliance with the ECRML.